SELF-IMAGE AND SEXUAL ACTIVITY OF PATIENTS IN TREATMENT FOR BREAST CANCER: A SYSTEMATIC REVIEW (CIPEEX, 2022)
BREAST ADENOCARCINOMA IS A TYPE OF CANCER WHICH SEVERELY IMPACTS A WOMAN€™S LIFE, BOTH PHYSICALLY AND PSYCHOSOCIALLY. THIS TYPE OF CANCER IS CAPABLE OF IMPACTING SELF-CONCEPT, FEMALE SEXUALITY AND EVEN FEMININITY. SEVERAL WOMEN DURING BREAST CANCER TREATMENT POSSESS A SELF-CONCEPT DISORDER DUE TO THE BREAST SOCIAL CONSTRUCT AS AN IMPORTANT AND SYMBOLIC ORGAN FOR FEMININITY, THUS IMPACTING SELF-ESTEEM OF PATIENTS WHO FEEL INSECURE IN THEIR SOCIAL AND MARITAL RELATIONSHIPS. THEREFORE, THE AIM OF THIS STUDY IS TO VERIFY THE INFLUENCES OF THERAPY AGAINST BREAST CANCER ON THE PSYCHOEMOTIONAL DIMENSION AND FEMALE SEXUALITY.
Keywords: Sexuality; Quality of life; Breast neoplasms; Body image